Penerapan Sistem Informasi Industri di Human Resource Department di PT. XYZ - Edhiargo Toyosito, Rakay; Yazid Bustommy, Abby; Bagus Sumantri, Ida (Universitas Tangerang Raya, 2022)
Information systems at this time have made human life easier. Every company, government and educational institution definitely needs an information system because it is very beneficial for many parties. So now many companies are using information systems to support their company's activities. Because the information system itself can make it easier to manage company activities.